2000
DOI: 10.1111/j.1651-2227.2000.tb01216.x
|View full text |Cite
|
Sign up to set email alerts
|

Head growth in Rett syndrome

Abstract: The longitudinal development of head growth was investigated in girls with Rett syndrome. Measurements were taken retrospectively from different kinds of records. Growth retardation was expressed in standard deviation (SD) scores. In classic types, the mean head circumference fell successively to 2 SD scores below the norm at the age of 4 y. After the age of 8 y it stabilized close to –3 SD scores. The degree of deceleration correlated strongly to the age at which a deceleration of 1 SD score had occurred. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…Post-mortem studies of RTT patients revealed lower hippocampal spine density and reductions in dendritic branching of CA1 pyramidal cells and decreased spine density in the frontal, parietal, temporal, and occipital cortices (Armstrong et al, 1995;Armstrong, 2001;Belichenko and Dahlstrom, 1995). In addition, neuronal cell size (Chen et al, 2001;Hagberg et al, 2001) and white matter volume are reduced, whereas there is also evidence of cerebellar degeneration in RTT patients (Reardon et al, 2010). Mouse models of RTT have demonstrated similar reductions in dendritic complexity and cell size (Fukuda et al, 2005;Kishi and Macklis, 2004;Kriaucionis and Bird, 2003;Zoghbi, 2003) with smaller cell size and increased density of neurons (Chen et al, 2001) and reduced brain volume in the amygdala, hippocampus, and striatum in loss-of-function models (Stearns et al, 2007).…”
Section: Loss-or Gain-of-mecp2 Function Has Deleterious Effects On Dementioning
confidence: 99%
“…Post-mortem studies of RTT patients revealed lower hippocampal spine density and reductions in dendritic branching of CA1 pyramidal cells and decreased spine density in the frontal, parietal, temporal, and occipital cortices (Armstrong et al, 1995;Armstrong, 2001;Belichenko and Dahlstrom, 1995). In addition, neuronal cell size (Chen et al, 2001;Hagberg et al, 2001) and white matter volume are reduced, whereas there is also evidence of cerebellar degeneration in RTT patients (Reardon et al, 2010). Mouse models of RTT have demonstrated similar reductions in dendritic complexity and cell size (Fukuda et al, 2005;Kishi and Macklis, 2004;Kriaucionis and Bird, 2003;Zoghbi, 2003) with smaller cell size and increased density of neurons (Chen et al, 2001) and reduced brain volume in the amygdala, hippocampus, and striatum in loss-of-function models (Stearns et al, 2007).…”
Section: Loss-or Gain-of-mecp2 Function Has Deleterious Effects On Dementioning
confidence: 99%
“…Early development was not invariably normal 109 nor did deceleration of head growth always occur. 110 In 2010 a further set of criteria was introduced in the hope of clarifying some of the differences in terminology between Europe and North America (see Fig. 1).…”
Section: Clinical Features and Diagnosismentioning
confidence: 99%
“…36 However, most individuals with RTT after age 7Ϫ8 years have measurements less than Ϫ3 SD compared with those for unaffected individuals. 30,35 Statistical comparisons beyond Ϫ3 SD contain insufficient empirical data and are imprecise. 37 This study addressed methodologic concerns by recruiting 7% of the RTT population in the United States, ranging in disease severity and coming from many racial, ethnic, and geographical backgrounds, through the International Rett Syndrome Foundation.…”
Section: Figure 1 Height and Weight In Unaffected Children (Orange) Amentioning
confidence: 99%
“…DISCUSSION Growth studies in RTT have been limited to small populations 1,[27][28][29] or specific anthropometric measurements, 30,31 and most were performed before MECP2 mutations were discovered or used statistical methods insufficient for calculating z scores. This study demonstrates that the patterns of growth in RTT are different from those in unaffected individuals.…”
Section: Figure 1 Height and Weight In Unaffected Children (Orange) Amentioning
confidence: 99%